Abrasive wear failure analysis of tungsten carbide hard facing on carbon steel blade - Mohd Tobi, A. L.; Kamdi, Z.; Ismail, M. I.; Nagentrau, M.; Roslan, L. N. H.; Mohamad, Z.; Omar, A. S.; Abdul Latif, N. (IOP Publishing, 2017)
This study investigate the abrasive wear failure of tungsten carbide hardfacing on continuous digester (CD) blade (carbon steel) in an environment of sulphuric acid and ilmenite ore mixture. Comparison being made on the hardness, thickness and microstructural of the hardfacing between unworn and 3 months old worn blade on few locations around the blade. The cross sections of the blade revealed non-uniform coverage of the hardfacing on the blade for both worn and unworn blade. The edge of the blade has the least amount of hardfacing thickness which with time acts as the point of failure during the wear process. The hardness obtained from both the unworn and worn samples are around 25% lower from the hardfacing electrode manufacturer’s hardness specification. Microstructural micrograph analysis of the hardfacing revealed non uniform size carbide with non-uniform distributed of carbide in the hardfacing layer.